A novel C202F mutation in the connexin26 gene (GJB2) associated with autosomal dominant isolated hearing loss. Issue 5 (1st May 2000) - Morlé, Laurette; Bozon, Muriel; Alloisio, Nicole; Latour, Philippe; Vandenberghe, Antoon; Plauchu, Henri; Collet, Lionel; Edery, Patrick; Godet, Jacqueline; Lina-Granade, Geneviève
Abstract : Mutations in the GJB2 gene encoding connexin26 (CX26) account for up to 50% of cases of autosomal recessive hearing loss. In contrast, only one GJB2 mutation has been reported to date in an autosomal dominant form of isolated prelingual hearing loss. We report here a novel heterozygous 605G→T mutation in GJB2 in all affected members of a large family with late childhood onset of autosomal dominant isolated hearing loss. The resulting C202F substitution, which lies in the fourth (M4) transmembrane domain of CX26, may impair connexin oligomerisation. Finally, our study suggests that GJB2 should be screened for heterozygous mutations in patients with autosomal dominant isolated hearing impairment, whatever the severity of the disease.